Synchronous endometrioid carcinoma of the endometrium and small cell neuroendocrine carcinoma of the cervix: a rare combination. (8th November 2018) - Nakra, Tripti; Biswas, Rituparna; Pandey, Rambha; Yadav, Rajni
Abstract : Synchronous multiple primaries of female genital tract are uncommon, with the most frequently encountered combination being of endometrium and ovary. Concurrent primary tumours of endometrium and cervix are rare. We report a case of coexistent endometrioid carcinoma of the endometrium and small cell neuroendocrine carcinoma of the cervix in 48-year-old woman who presented with menometrorrhagia and was detected to have metastases to distant sites on imaging. She underwent multimodality treatment which resulted in a significant reduction in the tumour bulk.